ADRB2 Arg16Gly polymorphism, lung function, and mortality: results from the Atherosclerosis Risk in Communities study. - Jill M Ferdinands; David M Mannino; Marta L Gwinn; Molly S Bray (PLoS ONE)
Background Growing evidence suggests that the Arg16Arg genotype of the beta-2 adrenergic receptor gene may be associated with adverse effects of beta-agonist therapy. We sought to examine the association of beta-agonist use and the Arg16Gly polymorphism with lung function and mortality among participants in the Atherosclerosis Risk in Communities study. Methodology and principal findings We genotyped study participants and analyzed the association of the Arg16Gly polymorphism and beta-agonist use with lung function at baseline and clinical examination three years later and with all-cause mortality during 10 years of follow-up. Lung function was characterized by percent-predicted forced expiratory volume in 1 second. Associations were examined separately for blacks and whites. Black beta-agonist users with the Arg/Arg genotype had better lung function at baseline and at the second clinical visit than those with Arg/Gly and Gly/Gly genotypes. Adjusted mean percent-predicted FEV(1) was 21% higher in Arg/Arg subjects compared to Gly/Gly at baseline (p = 0.01) and 20% higher than Gly/Gly at visit 2 (p = 0.01). Arg/Gly subjects had adjusted percent-predicted FEV(1) 17% lower than Arg/Arg at baseline but were similar to Arg/Arg subjects at visit 2. Although black beta-agonist users with the Arg/Arg genotype appeared to have better crude survival rates, the association between genotype and all-cause mortality was inconclusive. We found no difference in lung function or mortality by genotype among blacks who did not use beta-agonists or among whites, regardless of beta-agonist use. Conclusions Black beta-agonist users with the ADRB2 Arg16Arg genotype had better lung function, and, possibly, better overall survival compared to black beta-agonist users with the Gly16Gly genotype. Our findings highlight the need for additional studies of sufficient size and statistical power to allow examination of outcomes among beta-agonist users of different races and genotypes.